PERGESERAN PERAN NEGARA DALAM PELAYANAN KESEHATAN DI KOTA KUPANG (STUDI KASUS: RSUD PROF. DR. W. Z. JOHANNES PADA PERIODE 2016-2020) - Mandala Putra, Atanasius Bagas; Erawan, I Ketut Putra; Noak, Piers Andreas (Jurnal Nawala Politika, 2021)
This study describe the role of the state shifted to privatization in Prof. Dr. W. Z. Johannes Hospital in 2016-2020. This problem is related to the role of the state as someone in charge of health insurance. This study uses theory of Privatization according to Savas, which focuses on reducing the role of the state and increasing the role of the private sector. The method and type of research is descriptive qualitative. The results of this study indicate that the role of the state as a health service provider has been implemented by BPJS Kesehatan. BLUD regulation has changed from a traditional to semi-private, however the changed has not been able to carried out by the Hospital because they still need APBD funds from the government. There’s also a problem with the availability of medicine in the hospital and the patient of BPJS Kesehatan must buy medicine outside the hospital. Keyword :Role of The State, Privatization, Health Service, Prof. Dr. W. Z. Johannes Hospital